2020
DOI: 10.13189/ujer.2020.080245
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Use of Grammar among Indonesian Second Language Learners of Arabic: Focus on Grammatical Gender Agreement

Abstract: This study investigates spoken production of Indonesian L2 learners of Arabic examined by the frameworks of Local Impairment Hypothesis (LIH) and Missing Surface Inflectional Hypothesis (MSIH). Because the feature strength is absent from L2 learners, LIH claims that they will suffer from impairment at any stages of development. Accordingly, all participants will experience variability in the use of gender agreement. Conversely, MSIH predicts that such impairment L2 learners exhibit is superficial. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The findings of the study suggested that student's positive attitude toward role play activity will enhance their performance in Arabic learning, especially speaking skills [18]. As mentioned by Wildi and Titin [1], grammatical aspect such as gender agreement is one of the most problematic in oral production. However language activity may reduce the problem when it comes into practice.…”
Section: Illustration 2 Dimensions On Speaking Skills Studies For Armentioning
confidence: 75%
“…The findings of the study suggested that student's positive attitude toward role play activity will enhance their performance in Arabic learning, especially speaking skills [18]. As mentioned by Wildi and Titin [1], grammatical aspect such as gender agreement is one of the most problematic in oral production. However language activity may reduce the problem when it comes into practice.…”
Section: Illustration 2 Dimensions On Speaking Skills Studies For Armentioning
confidence: 75%
“…Strategy to revitalize local wisdom consist of all efforts to keep loyal to the glorious teaching of local culture and its development to strengthen national character. [23] In this context, the writer emphasizes on revitalization of local wisdom that is included in makna gandul and symbols of Arabic grammatical sciences that using Arabic language, and then reconstructing them using new model and approach [24], which is by translating it into Indonesian [25] as unifying language. The aim is to make santri who study in this type E of boarding school can understand and read kitab kuning without being adapted to local language of boarding school.…”
Section: Reconstruction and Revitalization Of Makna Gandul Kiab Kuninmentioning
confidence: 99%